Modeling of signals, linear links and responses of telecommunications and radioelectronics systems in frequency domain - N. I. Belenkevich; V. A. Ilyinkov; D. A. Kukhmar (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Single mathematical models of the signals' frequency characteristics, links and responses of telecommunications and radioelectronics systems were suggested. These models embody and epitomize amplitude- and phase-frequency responses of all types of linear links, as well as the amplitude and phase spectrums of no periodic finite, no periodic eternal, periodic signals, and the responses corresponding to them. The algorithm for calculation of frequency and energy characteristics has been developed on the basics of suggested models. The algorithm allows creation of effective automated simulations procedure of signals, links and responses in frequency domain.